BIODIVERSITY AND HABITAT COMPLEXITY ANALYSIS AT DIFFERENT LAND COVERS IN COAL MINING AREA, SITE SEBAKIS, NUNUKAN DISTRICT - Chairunissa (Nim : 11514018), Kanya
Biodiversity is one of the main factor that should be considered in post mining land reclamation for its basic role in providing ecosystem services. In contrast to its importance, biodiversity is potential to be degraded, due to land clearance from mining extraction that caused the loss of vegetation above ground. This research’s aims are to determine vegetation structure community, plant and arthropod biodiversity, also habitat complexity in four different land covers. Plant biodiversity is collected using 20 plots 20 m x 20 m (tree), 10 m x 10 m (pole), 5 m x 5 m (sapling and shrub), and 2 m x 2 m (seedling and herb). Above ground arthropod biodiversity is collected using pitfall trap method, which is a set (each consist four) of glasses that are filled with detergent water in also 20 plots. Both plots are placed in four different land covers which are primary forest, secondary forest, palm oil plantation, and open land. Data analysis using Shannon Index (H’), Importance Value Index (INP), and Habitat Complexity Index. Research results conduct that primary forest has the highest plant diversity value (2,52). The highest importance value of trees in primary forest is Dipterocarpus sp., in secondary forest is Acacia mangium, and not found in palm oil plantation. The highest importance value of shrub is not found in primary forest, Melastoma malabathricum in secondary forest, and Clidemia hirta in palm oil plantation. The highest importance value of herbs is no domination in primary forest, Scleria sumatrensis in secondary forest and Blechnum sp. in palm oil plantation. There are 88 species and 33 families found among four land covers. Secondary forest has the highest number of arthropod individuals (1688 individual), meanwhile palm oil plantation has the highest number of species and families (47 species and 20 family). Palm oil plantation has the highest arthropod diversity (2,51). Formicidae is the family with highest individual and species number. Both Formicidae and Gryllidae are found in all land covers. Primary forest has the highest habitat complexity index (7), followed by secondary forest (6,4), palm oil plantation (6), and the lowest is open land (0), hence primary forest can provide complex habitat more than three other land covers.